Ẕikr-i Mīr : yaʻnī, Ḥaz̤rat Mīr Taqī Mīr kī ḵẖudnavisht savāniḥ ʻumrī - Mīr, Mīr Taqī, d. 1810 (SAMP early 20th-century Indian books project ;, 1928)
Autobiography of Mīr Taqī Mīr, d. 1810, Urdu poet.